Students’ contribution to scientific papers publication in SciELO-Peru’s indexed medical journals, 1997 – 2005 - Huamaní, Charles (2008)
Objective: To quantify student participation in the publication of original contributions in Peruvian medical journals indexed to SciELO Peru. Design: Retrospective observational study. Setting: Archives of the UNMSM Faculty of Medicine and in www.scielo.org.pe. Population: Original papers, short communications (included case reports) and letters to the editor published from 1997 through 2005 in updated quarterly journals. Interventions: Review of authors affiliation (student or professional; sex, university and professional studies of origin), article type and research area (clinical, biomedical, public health). Principal outcome measures: Frequency and percentage of papers with student participation. Results: We included 865 original contributions from four journals; in 4,5% (39) students participated in the authorship, 74% (29/39) were original papers, 10 short communications and there was no letter to the editor. Anales de la Facultad de Medicina was the journal that published most of the student papers (6,6%). The median was five student papers per year. Ten articles were done only by students, 87% came from three universities (Universidad Nacional Mayor de San Marcos, Universidad Peruana Cayetano Heredia, and Universidad Privada Antenor Orrego) and 58% pertained to the clinical area. The majority (72%) of the authors was male. Conclusions: Student participation in papers published in Peruvian medical journals is poor. We recommend training students in publishing their research; this course should be included in the medical curricula.